DEVELOPMENT OF COMPETITION STRATEGY OF DAIRY ENTERPRISESS - SOKYRNYK, IRINA; ROMANYUK, OLENA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The purpose of the article is to generalize scientific approaches to the essence of competition strategy and determine the main features of its formation by dairy enterprises. The paper considers the development of competition strategy, which is part of the strategic management system. It is noted that the result of strategic management of the dairy enterprise is a system of strategies, a system of strategic changes and strategic potential for their implementation. The theoretical aspects of the competition strategy are analyzed and it is determined that its components for the dairy enterprise are the competition strategy in the resource market and the competition strategy in the markets. Components of competition strategy are formed taking into account two groups of strategic goals of the enterprise: regarding raw material suppliers and strategic goals related to the company’s products and market promotion. Each of these components contains strategic decisions and changes for their implementation in relation to support of strengthening, creating and developing competitive advantages. Given that competition in the raw materials market is characterized by a limited number of entities - suppliers of quality raw materials, the authors believe that the ability to compete for sources of raw materials determines the content of the competition strategy in terms of prices, product range, methods of competition in the market. Characteristics of environmental factors are given, and their strategic influence on the choice of competition strategy of the enterprise is determined. An algorithm for developing a competition strategy is proposed. For effective manage the implementation of competition strategy, the enterprise must respond flexibly and proactively to external opportunities and threats. It is also advisable to apply the decomposition of management decisions from the level of competition strategy to the level of the portfolio of strategic change.